The Existence and Role of the General Election Supervisory Committee (Panwaslu) of Cigemblong District as the Organizer of the 2024 Simultaneous General Election - Humaeroh, Siti; Ridwan, Ujang (Educational Studies and Research Journal, 2024)
This study aims to analyze the existence and role of the Election Supervisory Committee (Panwaslu) of Cigemblong District in the implementation of the 2024 Simultaneous General Election. A descriptive qualitative method with a field research approach was employed. Data were collected through observation, interviews, and documentation involving nine informants, including election organizers, supporters, and community members. Purposive sampling was used to select knowledgeable respondents, while data analysis involved reduction, presentation, and conclusion drawing. The results show that Panwaslu of Cigemblong District holds a significant existence within the sub-district election administration structure. Its presence is recognized by the community due to its active role in supervising each election stage, responding to reported violations, and maintaining communication with local stakeholders. Nevertheless, Panwaslu still faces challenges related to limited human resources and logistical support, affecting the effectiveness of supervision. The study highlights the importance of strengthening institutional capacity and professional competence to enhance the integrity and accountability of election oversight in future elections.